2003
DOI: 10.1074/jbc.m307761200
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor Binding Modulates the Conformational Stabilities and Unfolding Patterns of NAD+-dependent DNA Ligases from Escherichia coli and Thermus scotoductus

Abstract: DNA ligases are important enzymes required for cellular processes such as DNA replication, recombination, and repair. NAD ؉ -dependent DNA ligases are essentially restricted to eubacteria, thus constituting an attractive target in the development of novel antibiotics. Although such a project might involve the systematic testing of a vast number of chemical compounds, it can essentially gain from the preliminary deciphering of the conformational stability and structural perturbations associated with the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…Although the relationship of the amino acid mutation to enzymic activity or structure has not been directly demonstrated at this time, the molecular model suggests that the alteration of amino acid 15 from Leu to Phe may alter the packing involving a-helix A, which is close to the N-terminus. This bi-helix is implicated in the binding of NAD + to LigA (Georlette et al, 2003;Sriskanda & Shuman, 2002), supporting our proposal that the temperature sensitivity of LigA251 is a consequence of factors altering the rate of adenylation of the protein.…”
Section: Nadsupporting
confidence: 63%
See 1 more Smart Citation
“…Although the relationship of the amino acid mutation to enzymic activity or structure has not been directly demonstrated at this time, the molecular model suggests that the alteration of amino acid 15 from Leu to Phe may alter the packing involving a-helix A, which is close to the N-terminus. This bi-helix is implicated in the binding of NAD + to LigA (Georlette et al, 2003;Sriskanda & Shuman, 2002), supporting our proposal that the temperature sensitivity of LigA251 is a consequence of factors altering the rate of adenylation of the protein.…”
Section: Nadsupporting
confidence: 63%
“…Thus, NAD + -DNA ligases have been suggested as possible targets for broad-spectrum antibacterial compounds (Georlette et al, 2003;Gong et al, 2004;Kaczmarek et al, 2001;Lee et al, 2000;Singleton et al, 1999;Sriskanda & Shuman, 2002). If substantial progress is to be made in the development of inhibitors that are specific to NAD + -DNA ligases, it is vital that in vivo models are utilized to test the efficacy of such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the former, even at early stages of ligase IV/XRCC4 purification, only small quantities of labeled protein are detected upon incubation with Mg 2+ and [R-32 P]ATP; consistent with the latter, we have found the unadenylylated form of ligase IV (in both its free and XRCC4-complexed forms) to be less stable than the adenylylated form during extended periods of incubation at 37°C (data not shown). Studies with other DNA ligases have demonstrated the presence of a conformational change upon enzyme adenylylation (39)(40)(41)(42); in some cases, this was found to enhance thermostability (41,42). In light of the above, the inclusion of a Mg 2+ /ATP incubation step at an early phase of protein purification could conceivably enhance the yield of ligase IV.…”
Section: Expression/purification Of the Ligase Iv/xrcc4mentioning
confidence: 99%
“…Structural studies have revealed that these enzymes are generally highly fold flexible and therefore less rigid (Georlette et al, 2003(Georlette et al, , 2004Collins et al, 2005). Cold-active enzymes are also characterized by stacking of small amino acids around the catalytic residues (Feller et al, 1992;Davail et al, 1994).…”
Section: Structural Modeling Reveals a Putative Ibsmentioning
confidence: 99%